COVID-19 mass media coverage in English and public reactions: a West-East comparison via Facebook posts - Pratama, Ahmad R.; Firmansyah, Firman M. (PeerJ Computer Science, 2022)
Newspapers and other mass media outlets are critical in shaping public opinion on a variety of contemporary issues, including the COVID-19 pandemic. This study examines how the pandemic is portrayed in the news and how the public reacted differently in the West and East using archival data from Facebook posts about COVID-19 news by English-language mass media between January 2020 and April 2022 (N = 711,646). Specifically, we employed the Valence Aware Dictionary and sEntiment Reasoner (Vader) to measure the news tone on each COVID-19 news item shared on Facebook by mass media outlets. In addition, we calculated a polarity score based on Facebook special reactions (i.e., love, angry, sad, wow, haha, and care) received by each post to measure public reactions toward it. We discovered that people in Western countries reacted significantly more negatively to COVID-19 news than their East counterparts, despite the fact that the news itself, in aggregate, generally contained a relatively similar level of neutral tone in both West and East media. The implications of these distinctions are discussed in greater detail.
Keywords: Facebook posts; Public reactions; COVID-19 news; Mass media; Sentiment analysis; West-East; Individualism; Collectivism; News tone